Changing an industry: leading equality in the investment and savings industry. Issue 3 (16th June 2021) - Butler, Steve; Smith, Simon M.
Abstract : Purpose: The purpose of this paper is to explore the impact of the Diversity Project, a cross company initiative that has been applied in the investment and savings profession to accelerate progress towards a more inclusive culture across the industry. This is with a view to providing a template for other industries considering impactful change. Design/methodology/approach: This paper considers the approach taken by the investment and savings industry to drive change towards a more inclusive culture by using a summative content analysis approach. The authors framework this application using Sustainable Development Goal 10 (reduced inequalities) to increase relevance and contribution beyond this context. Findings: The Diversity Project demonstrates numerous examples of driving change within the investment and savings industry by galvanising cross company support for events, publications, charters and action. These experiences will provide policymakers and practitioners in other industrial sectors insight to achieve similar change. Originality/value: The Diversity Project established in 2016 has gained significant traction in the investment and savings industry through membership of 70 firms and 30 partner firms, supporting 18 cross company diversity and inclusion work streams focussed on developing collaborative and cohesive action plans.